Gangguan Emosi Tokoh Sheila dalam Novel The Tiger’s Child Karya Torey Hayden - Puspa Sari; Ramli (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2023)
The objective of this study was to identify and understand comprehensively the emotional disorder happened to Sheila as the main character in The Tiger’s Child novel by Torey Heyden. This qualitative study used psychoanalysis method carried out in May – July 2022. The data were collected from the novel as a source of data. The data of emotional disorder were identified by reading the novel repeatedly and thoroughly. The research found 6 types of emotional disorder: anger was 23 (35,94%), Sadness was 14 (21.88%), loneliness was 9 (14.06%), apathy was 8 (12.50%), labil was 7 (10.94%), and anhedonia was 3 (4.69%). And the dominant emotional disorder experienced by Sheila was Anger. In addition, all emotional disorders were caused environmental and family factors.